Removal of Phenol and Aniline from Aqueous Solutions by Using Adsorption on to Pistacia terebinthus: Study of Adsorption Isotherm and Kinetics - shahin ahmadi; somaye rahdar (Mazandaran University of Medical Sciences, 2017)
Introduction and purpose: Aniline and phenol are used in a wide range of industries, namely dye material, rubber, pesticide, plastic, and paint industries. These chemicals are released to the environment via effluent. This study aimed to investigate the efficiency of modified Pistacia terebinthus in removal of phenol and aniline from aqueous solutions. Methods: In this experimental-laboratory study, effects of initial aniline and phenol concentrations, Pistacia terebinthus dosage, time, pH, and interference compounds on efficiency of aniline and phenol removal were investigated. Data evaluated for compliance with the isotherm (Langmuir, Freundlich, and Temkin) and kinetic (Pseudo second-order, Pseudo First-order and Intraparticcle diffusion) models Results: Our data showed that removal efficiency decreased with raising pH. The optimum condition for removal of aniline was pH=6, initial concentration= 50 mg/L, and contact time= 45 min, while for phenol it was pH=4, concentration= 50 mg/L, and contact time= 30 min. Adsorption isotherm data show that the fluoride sorption followed the freundlich isotherm. Aniline and phenol adsorption kinetics onto modified Pistacia terebinthus follows pseudo-second-order model. Conclusion: Pistacia terebinthus is an effective factor in removal of aniline and phenol from water and effluent.